Electron emission spectra of U28+-ions colliding with gaseous targets. (July 2015) - Hillenbrand, P-M; Hagmann, S; Monti, J M; Rivarola, R D; Blumenhagen, K-H; Brandau, C; Chen, W; DuBois, R D; Gumberidze, A; Guo, D L; Lestinsky, M; Litvinov, Yu A; et al.
Synopsis: The electron-loss to continuum has been studied experimentally and theoretically for the collision systems U 28+ + H2 at a collision energy of 50 MeV/u, U 28+ + N2 at 30 MeV/u, and U 28+ + Xe at 50 MeV/u.